2018
DOI: 10.1016/j.tranon.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A New Mechanism of Prosurvival and Drug Resistance in Multiple Myeloma

Abstract: Autophagy is an intracellular self-degradative process that balances cell energy source and regulates tissue homeostasis. In physiological condition, autophagy funnels cytoplasmic constituents to autophagolysosomes for degradation and is an alternative way for cell-death behavior. Here, we inspected autophagy as a prosurvival mechanism essential for drug resistance in multiple myeloma (MM). Accordingly, autophagy inhibitors used in association to conventional anti-MM drugs might enforce the effect against resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 98 publications
(111 reference statements)
1
53
0
3
Order By: Relevance
“…Myeloma PCs are characterized by reduced proteasome expression but an increased proteasome workload (likely due to immunoglobulin (Ig) synthesis) and greater apoptotic sensitivity to bortezomib [44,45]. In the presence of a proteasome inhibitor, a potential PC survival strategy is the activation of autophagy, an alternative cellular mechanism of protein degradation [19]. Proteasome inhibition by bortezomib in tumor PCs results in the accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER), a response referred to as ER stress, accompanied by the overproduction of reactive oxygen species in the ER, and the activation of unfolded protein cascade components, especially the protein kinase R-like (PKR-like) ER kinase, resulting in the induction of autophagy [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloma PCs are characterized by reduced proteasome expression but an increased proteasome workload (likely due to immunoglobulin (Ig) synthesis) and greater apoptotic sensitivity to bortezomib [44,45]. In the presence of a proteasome inhibitor, a potential PC survival strategy is the activation of autophagy, an alternative cellular mechanism of protein degradation [19]. Proteasome inhibition by bortezomib in tumor PCs results in the accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER), a response referred to as ER stress, accompanied by the overproduction of reactive oxygen species in the ER, and the activation of unfolded protein cascade components, especially the protein kinase R-like (PKR-like) ER kinase, resulting in the induction of autophagy [46].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the development of new therapeutic strategies, such as combination therapies, that overcome bortezomib resistance is urgently needed [17,18]. Proto-oncogene, serine/threonine kinase Bortezomib resistance may be mediated by the activation of the autophagy pathway, as an alternative mechanism of protein degradation [19,20]. Autophagy is a catabolic process that is well conserved among all mammals because it modulates homeostasis, by clearing and recycling damaged or useless cell constituents [21].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an intracellular self-degradative process that plays a key role in regulating cell growth and metabolism. 13 Unlike the ubiquitin-proteasome system, which is also involved in cell degradation, the substrate of autophagy is endogenous, and autophagy is the process responsible for cellular degeneration and the destruction of certain organelles or the local cytoplasm. 14 PAK proteins are critical modulators of nuclear signal transduction and cytoskeletal reorganization; among the PAK proteins, p21 (RAC1)-activated kinase 1 (PAK1) modulates a wide range of signals involved in a large number of biological activities.…”
Section: Ivermectin Induces Cell Death In Cancer Cellsmentioning
confidence: 99%
“…Thus, activation of autophagic cell death may represent a promising approach for treatment of MM (32)(33)(34)(35)(36). Recent studies have demonstrated that autophagy mediates drug resistance in MM cells and leads to development of clinical complications for MM, while inhibition of autophagy may reverse the response to drugs (37,38). However, the clinical role, particularly the prognostic role of ARGs in MM, has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%